The Influence Of E-Commerce On Buying And Selling And Promotional Media Case Study: Clothing Shop - Nandini; Nurhanifah; Vira Nabila; Mega Aulia Putri; Muhammad Rifky Azhar Hasibuan; Muhammad Zidan Sayrevi (Penerbit Hellow Pustaka, 2025)
This research aims to see how influential clothing shops are that use E-commerce as a means of marketing and promotion, not only that, E-commerce is often used to increase the brand image of what has been produced. Expanding marketing reach so that many consumers know the product, trying to provide satisfaction to potential buyers or customers by making good quality goods, not fake. This research uses quantitative, distributing questionnaires to the media so that they are filled in by the person who receives the questionnaire. Then, collect several responses from one person to another. This research method is not far from the percentage of media consumer satisfaction with buying and selling carried out via e-commerce or online. The results of this research show that many people use media as a means of buying and selling transactions because it is easy for transactions to be carried out without having to go out, E-commerce has its own target market, namely those who use media, with the existence of E-commerce it can expand market reach so that anywhere Well-to-do people can make transactions using this electronic device.